Interculturalising the curriculum: faculty professional development. Issue 5 (2nd September 2016) - Garson, Kyra; Bourassa, Emma; Odgers, Todd
Abstract: This paper describes faculty perceptions of the impacts of a professional development (PD) programme for faculty called Interculturalising the curriculum. Over 70 faculty members have participated since 2008. Participants in the study represented four cohorts from 2008, 2011, 2012, 2013, from a broad range of academic disciplines. We begin with a review of the literature relevant to the rationale for, and challenges of, intercultural faculty development. We describe the theoretical frameworks and design of the programme. Next we present the results of a survey and one-on-one interviews with 20 past participants. The findings of the study combined with real changes in pedagogy and curriculum provide evidence that well-planned, theoretically grounded, intercultural PD for faculty can promote long-lasting impacts for both the educators and their students.